Legal nature of an official act of the President of the Republic of Poland pronouncing retirement of the Supreme Court judge (Ius Novum, 2020)
The analysis of the legal nature of an official act of the President of the Republic of Poland pronouncing the Supreme Court judge’s retirement results in a conclusion that the act of the President issued in accordance with Article 29 of the Act on the Supreme Court is authoritative and declaratory. Its content stipulates a solution concerning legal premises that result in a judge’s retirement. In this scope, the President of the Republic of Poland acts as a public administration body in the functional meaning because the solution pronounces the change of the judge’s service relationship. The President’s action in this respect is not a presidential prerogative under Article 144 para. 3(17) of the Constitution of the Republic of Poland. This means that this type of an official act issued as part of public administration activities, stipulated under Article 184 of the Constitution, is subject to control by administrative courts.
Keywords: acts of the President of the Republic of Poland; declaration of retirement; public administration body; jurisdiction of the court